User involvement and entrepreneurial action - Heiskanen, Eva; Repo, Petteri (Human Technology, 2007)
Involving users in the innovation process is a subject of much research, experimentation, and debate. Less attention has been given to the limits to user involvement that ensue from specific organizational characteristics. This article explores barriers to the utilization of users' input in two small companies developing interactive digital applications. We contrast our findings to earlier research involving large companies to identify features of entrepreneurial sensemaking and action that influence the utilization of users' input. We find that the small companies follow a distinct action rationality, leading to rapid implementation of some user inputs, and defensiveness toward others. Both sets of data also reveal common features that are often overlooked in the literature. We reconceptualize user involvement as a form of interaction between users and innovating companies that is facilitated and constrained by micro-sociological processes, on the one hand, and the nature of the competitive environment, on the other.